Food Intolerance of Unknown Origin: Caused by Mucosal Inflammation? A Pilot Study. Issue 2 (17th February 2021) - Dieterich, Walburga; Tietz, Esther; Kohl, Matthias; Konturek, Peter C.; Rath, Timo; Neurath, Markus F.; Zopf, Yurdagül
Abstract : INTRODUCTION: The prevalence of patients with food intolerance (FI) has increased significantly. Immunoglobulin (Ig)E-mediated food allergies (FAs) are detected by determining IgE antibodies and skin prick test. Carbohydrate malabsorptions are clarified with breath tests. However, these diagnostic measures cannot capture all intolerances and have limitations in case of gut-mediated FI. The aims of this pilot study were to evaluate different methods to determine intestinal mucosal IgE in patients with FA and to characterize the intestinal mucosa in patients with FI of unknown origin (FH). METHODS: Patients with FA and FH were compared with healthy controls. To determine the IgE antibodies and the cytokines tumor necrosis factor (TNF)-α and interferon (IFN)-γ of the intestinal mucosal, a lavage was performed as part of an ileocolonoscopy and samples were taken using the cytobrush and biopsy forceps. In a subgroup, mucosal samples were also taken from the duodenum. RESULTS: Data in homogenates of intestinal mucosal samples yielded the highest sensitivity for IgE antibody titers compared with lavage and cytobrush. Patients with FA presented increased intestinal TNF-α and low IFN-γ values. This was in contrast to FH patients, who showed low intestinal IgE antibodies and TNF-α levels, but increased IFN-γ values. DISCUSSION: The determination of IgE antibodies to diagnose intestinal IgE-mediated FA is most reliable in intestinal mucosal samples. Increased TNF-α and low IFN-γ levels in patients with FA characterize an allergic reaction. Decreased TNF-α and increased IFN-γ levels in patients with FH indicate an inflammation-related intolerance reaction (see Visual Abstract, Supplementary Digital Content 1, http://links.lww.com/CTG/A520 ).